O direito à saúde e a Lei nº 14.454/22: a natureza do rol de procedimentos e eventos em saúde da Agência Nacional de Saúde Suplementar à luz do direito do consumidor - Ebertz, Caroline (2024)
This article aims to analyze the nature of the list of health procedures and events of the National Supplementary Health Agency, from the perspective of consumer rights. The importance of the topic is justified by the recent legislation, which suffered a Direct Unconstitutionality Action, and its effects on consumer law. With this, we seek to investigate whether Law No. 14,454/22 represents an instrument to protect consumers. The aim is to study the right to health and health plans in the Brazilian legal system, to understand the legislative change promoted by Law No. 14,454/22, as well as the interpretation given by the Superior Court of Justice to the topic. The monographic method and case study are used, combined with a hermeneutic approach. Thus, it appears that the list provided for in Law No. 14,454/22 is exemplary, follows the dictates of the legal system and aims to protect consumers, with regard to the fundamental right to health. Furthermore, it facilitates access to treatments, in the broadest sense, for users of supplementary healthcare, given their legitimate expectations and vulnerability.